Web-based thesis title submission information system - Probo Sukadi Sumarno; Zulhipni Reno Saputra Elsi (International Journal Cister, 2022)
The rapid growth of the computer world has had a great impact in the world of information and telecommunications. It also triggers the rapid development of  information technology in order to provide convenience and facilities to support humans in an attempt to finish the job. The guidance system current thesis is generally manual, where students interact and face to face with the supervisor in a certain space and time. In the process, students are guided  by one supervisor appointed by the chairman of the study program. But the problem that often arises is the students and lecturers can not be met due to lack of compatibility between the two sides time and ignorance about the schedule student supervisor. Other than that, To overcome some of the weaknesses then designed an Online Application Final Guidance. This application aims to provide  convenience in the process of final guidance between students and lecturers. The system is web-based, with the  programming language used is PHP and uses a MySQL database